Some factors affecting scientific reserch activities of universities in Vietnam - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Each university has an assignment to perform three important missions: teaching, scientific research and social services. To improve their position, universities have different action plans to best develop these missions. Scientific research activity in universities needs to be particularly focused and developed simultaneously with teaching and social services. This is especially true for universities in developing countries as Vietnam. However, what are the key factors that may affect the university’s scientific research activity? The paper analyzes and clarifies some factors that may affect the university’s scientific research activity in Vietnam. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-size: 14px; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20080501